(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This paper mainly investigates the retraction phenomenon of yak hair fiber when stretched. To study the retraction of yak hair fiber with different stretching ratio and the effect of setting reagent, the samples were stretched by a self-made device, including force and position sensor. The retraction curves of yak hair fiber stretched with different drawing ratio up to 90% and different process phases, including stretching, first setting and second setting, were analyzed respectively. The results showed that there is rapid retraction in the early stage when the gripping force was lost, and the retraction velocity of stretched yak hair increased gradually with the stretching ratio increasing. Meanwhile, it was also found that the setting process could result in the reduction of the retraction quantity of stretched fiber evidently. In addition, the stress decay curve of yak hair fiber stretched 30, 60 and 90%, according to different process phase, were investigated likewise. The results for the stress decay of yak hair fiber bundles showed that the stress decay curve exhibited an exponential diversification and the velocity of stress decay had same results with the length retraction of yak hair fiber stretched.